In Situ Surface-Enhanced Raman Spectroscopy Investigation of the Passive Films That Form on Alloy 600, Alloy 690, Unalloyed Cr and Ni, and Alloys of Ni-Cr and Ni-Cr-Fe in Pressurized Water Nuclear Reactor Primary Water - Feng Wang; Thomas M. Devine (Corrosion and Materials Degradation, 2025)
Passive films that form on Alloy 600 and Alloy 690 during four hours in simulated Primary Water (PW) of Pressurized Water Nuclear Reactors (PWRs) at 320 °C were investigated by in situ surface-enhanced Raman spectroscopy (SERS). Similar tests conducted on unalloyed nickel, unalloyed chromium, and laboratory alloys of Ni-10Cr, Ni-20Cr, Ni-5Cr-8Fe, and Ni-10Cr-8Fe aided in assigning the peaks in the surface-enhanced Raman (SER) spectra of the passive films of Alloy 600 and Alloy 690. SERS indicates an inner layer (IL) of Cr2O3/CrOOH forms on both Alloy 600 and Alloy 690 and that Alloy 690’s IL was more protective against corrosion due to its greater resistance to ion transport. The outer layer (OL) of Alloy 600 consists of NiO and spinels, FeCr2O4—M(Cr,Fe)2O4. The OL of Alloy 690 contains no spinel. A comparison of SER spectra in 320 °C PWR PW to the spectra following cooling down to room temperature and after exposure to air indicates some differences between in situ films and ex situ films.